LEGAL MECHANISMS FOR PROTECTING THE PROVISIONS OF THE COPYRIGHT AGREEMENT (World Bulletin of Management and Law, 2025)
The article analyzes the general concept of civil liability for violation of the requirements of the copyright agreement under the legislation of the Republic of Uzbekistan. The article also examines the requirements that must be met by persons who have entered into an agreement to conclude a copyright agreement, and what liability may arise in the event of noncompliance with these requirements.